Clinical safety and efficacy of neoadjuvant combination chemotherapy of tranilast in advanced esophageal squamous cell carcinoma: Phase I/II study (TNAC). Issue 50 (11th December 2020) - Shiozaki, Atsushi; Kudou, Michihiro; Fujiwara, Hitoshi; Konishi, Hirotaka; Shimizu, Hiroki; Arita, Tomohiro; Kosuga, Toshiyuki; Yamamoto, Yusuke; Morimura, Ryo; Ikoma, Hisashi; Kuriu, Yoshiaki; Kubota, Takeshi; et al.
Abstract: Background: Transient receptor potential vanilloid 2 (TRPV2) was previously shown to play an important role in the maintenance of cancer stem cells, and its specific inhibitor, tranilast, also has potential as a targeted therapeutic agent for esophageal squamous cell carcinoma (ESCC). The present study is being conducted to confirm the safety and efficacy of the additional use of tranilast with conventional preoperative adjuvant chemotherapy for patients with advanced ESCC. Patients and methods: Between 56 and 59 patients aged between 20 and 74 years with clinically diagnosed Stage II or Stage III ESCC will be enrolled. Eligible patients will receive preoperative adjuvant chemotherapy, 2 cycles of combination therapy with cisplatin, 5-fluorouracil, and tranilast. Recruitment started in November 2019, with the final follow-up being planned for March 2029. One subject has been enrolled since October 21 st, 2020. The pathological therapeutic effect is the primary endpoint. The objective response rate, safety of preoperative adjuvant chemotherapy, recurrence-free survival (RFS), and overall survival (OS) are the secondary endpoints. RFS and OS will be calculated as the time from surgery to first recurrence and all-cause death, respectively. Ethics and dissemination: This protocol has been approved by the Institutional Review Boards of Kyoto Prefectural University of Medicine and all participating hospitals in August 30, 2019 (Number: CRB5180001). Written informed consent will be obtained from all patients before their registration, which is in accordance with the Declaration of Helsinki. The results of the present study will be disseminated via publication in peer-reviewed journals. Trial registration: Trial registration number jRCTs051190076